2011
DOI: 10.1530/rep-11-0114
|View full text |Cite
|
Sign up to set email alerts
|

Glucose transporters in the uterus: an analysis of tissue distribution and proposed physiological roles

Abstract: Facilitative glucose transport molecules (glucose transporters, GLUTs) are responsible for glucose transport across cellular membranes. Of the 14 family members, expression of nine has been reported in the murine uterus and seven in the human uterus. Some studies reveal that adequate glucose uptake and metabolism are essential for the proper differentiation of the uterine endometrium toward a receptive state capable of supporting embryo implantation. However, the mechanistic role of GLUTs in endometrial functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(101 citation statements)
references
References 59 publications
3
93
0
3
Order By: Relevance
“…Many of these are expressed in the uterus and some, including the ubiquitously expressed GLUT1, are elevated in endometrial cancer (25,(32)(33)(34)(35). GLUT1 is thought to contribute to basal glucose uptake in normal tissues, and upregulation of this transporter has been reported in many malignancies (36).…”
Section: Discussionmentioning
confidence: 99%
“…Many of these are expressed in the uterus and some, including the ubiquitously expressed GLUT1, are elevated in endometrial cancer (25,(32)(33)(34)(35). GLUT1 is thought to contribute to basal glucose uptake in normal tissues, and upregulation of this transporter has been reported in many malignancies (36).…”
Section: Discussionmentioning
confidence: 99%
“…Glucose metabolism is especially important in support of endometrial decidualization-the differentiation of the functionalis layer into the decidua rendering the endometrium capable of supporting a conceptus. 8,9,42,43 The initial step in glucose utilization is cellular uptake, which is mediated in human and murine uteri by facilitative glucose transporters, commonly referred to as GLUTs, however, now known as the SLC2A family, 9 specifically SLC2A 1,3,4, and 8. All SLC2As have shared characteristics but differ in tissue localization kinetics and substrate specificity.…”
Section: Glucose Metabolismmentioning
confidence: 99%
“…[5][6][7] The aforementioned dynamic changes that occur in the endometrium during the menstrual cycle are metabolically demanding, 8 and glucose metabolism has been proven to be important for the preparation of the endometrium for embryo implantation. [8][9][10] Specifically, it has been shown that endometrial stromal cell decidualization is dependent on increasing expression of glucose and facilitative glucose transporter (GLUT) 1. 11 In addition, hyperinsulinemia and insulin resistance have been shown to inhibit markers of endometrial receptivity such as insulin-like growth factor (IGF) type 1 receptors, and cause hyperandrogenism.…”
Section: Introductionmentioning
confidence: 99%
“…Cells can take up DHA using a different type of low-affinity transporters: the glucose transporters GLUT1, GLUT2, GLUT3, GLUT4, GLUT8, and GLUT10 (3,4). Among these GLUT isoforms, only GLUT1 has a ubiquitous distribution (5,6). Yet, GLUT1 is only expressed at modest levels by normal cells, except in the hematopoietic system and brain (5,6), indicating that DHA uptake is not a general mechanism for accumulating intracellular Vc throughout the body.…”
Section: Vcmentioning
confidence: 99%
“…Among these GLUT isoforms, only GLUT1 has a ubiquitous distribution (5,6). Yet, GLUT1 is only expressed at modest levels by normal cells, except in the hematopoietic system and brain (5,6), indicating that DHA uptake is not a general mechanism for accumulating intracellular Vc throughout the body. Notably, the levels of GLUT1 are increased potently under specific circumstances, including oncogenic signaling (7) and lowered oxygenation (hypoxia) (8).…”
Section: Vcmentioning
confidence: 99%